Map Collections as National Treasures - Häkli, Esko (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
Maps and cartographic presentations have always been highly valued, for the vital information they contain. Maps have been important to governments, companies and individuals. They have been used to defend and argue for political, military, economic and many other interests.